Characteristic analysis of adverse reactions of histone deacetylase inhibitors based on WHO-VigiAccess - Yin, Tongnan; Liu, Yuyu; Li, Chenwen; Feng, Xinran; Lin, Yumeng; Qu, Zhongyu (Frontiers in Pharmacology, 2025)
BackgroundThis study assessed the adverse drug reactions (ADRs) associated with HDAC inhibitors using the VigiAccess database maintained by the World Health Organization (WHO). Furthermore, it compared the ADR profiles of three different drugs to identify the one with the lowest individualized risk for patients.Materials and methodsData on adverse events of HDAC Inhibitors was retrieved from WHO-VigiAccess on 6 January 2025. We obtained data on age, gender, reporting year, and continent. Descriptive data related were calculated using Excel 2021. In this study, we used Excel software to analyze the characteristics of those who were harmed due to adverse reactions. For each drug, the reporting rate of adverse reactions was calculated by dividing the number of adverse reaction symptoms of this drug by the total number of adverse reaction reports. We listed the top 20 most frequent adverse reaction symptoms as common adverse reactions. By counting the frequency and proportion of these common adverse reactions, we conducted a comparative analysis of the adverse reaction situations of different drugs and classified them according to different types.ResultThe WHO-VigiAccess database received 796, 1254, and 1658 ADR reports for Chidamide, Romidepsin, and Vorinostat respectively by 2024, with a total of 3,708. Gender distribution was relatively balanced (male:female ratio 0.81:1), and the 45–64 age group had the highest reporting rates, mostly from the Americas. Chidamide had higher rates in certain disorders, Romidepsin in others, and Vorinostat in specific ones. Common ADRs included thrombocytopenia etc., with some differences in rates among drugs. Serious ADR proportions were 0% for Chidamide, 2.27% for Romidepsin, and 1.02% for Vorinostat. 37 common signals were found, with Investigations having the most. Each drug had different ADR preferred terms (PTs) in renal/urinary and metabolism/nutrition disorders, with varying numbers of distinctive symptoms.ConclusionCurrent comparative observational studies of these inhibitors indicate that there are both common and specific adverse reactions reported in the ADR data received by the WHO for these medications. Clinicians should enhance the rational use of these drugs by considering the characteristics of the reported ADRs.